Neighbours forever – or also cotenants: The Croatian language in the context of Slovene educational language policy - Tatjana Balažic Bulc (Rasprave: Časopis Instituta za Hrvatski Jezik i Jezikoslovlje, 2017)
Having signed different European and national documents, Slovenia accepted the ideas of European language policy based on multiculturalism and multilingualism. In this paper the method of critical discourse analysis is used to answer the question how these ideas are implemented both formally and legally in documents which enable the realization of language policy in education, with special attention being devoted to ideological concepts of these documents. The differences between the declarations in documents and practice are underlined, following the example of the Croatian language in Slovene primary school, where it primarily has the status of the foreign language. It is concluded that educational language policy in Slovenia generally supports learning and teaching of Croatian as a foreign language, but, unfortunately, without any planned strategy for foreign language teaching and also without systematic and coordinated concerns of competent institutions.